Foreign independent directors and the quality of legal institutions - Miletkov, Mihail; Poulsen, Annette; Wintoki, M. Babajide (Journal of International Business Studies, 2017)
Foreign directors can affect firm value through their advising and monitoring functions. However, the demand for these directors, as well as their effect on firm performance is likely to be influenced by firm- and country-level characteristics. In a large sample of non-US firms, we find that foreign directors are more likely to be associated with firms that have more foreign operations and an international shareholder base, and firms that are located in countries with a limited supply of potentially qualified domestic directors – countries with a smaller, less well-educated populace and lower levels of capital market development. We also find that the association between foreign directors and firm performance is more positive in countries with lower quality legal institutions, and when the director comes from a country with higher quality legal institutions than the firm’s host country. Our study highlights the importance of considering national demographic factors and levels of capital market development when modeling the supply and demand for foreign directors, and also underscores the importance of institutional quality in the foreign director’s home and host country when assessing the effect of that director on firm performance.